2017
DOI: 10.1016/j.ydbio.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cell origin, volume and arrangement are drivers of articular cartilage formation, morphogenesis and response to injury in mouse limbs

Abstract: Limb synovial joints are composed of distinct tissues, but it is unclear which progenitors produce those tissues and how articular cartilage acquires its functional postnatal organization characterized by chondrocyte columns, zone-specific cell volumes and anisotropic matrix. Using novel Gdf5CreERT2 (Gdf5-CE), Prg4-CE and Dkk3-CE mice mated to R26-Confetti or single-color reporters, we found that knee joint progenitors produced small non-migratory progenies and distinct local tissues over prenatal and postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 53 publications
3
174
0
Order By: Relevance
“…For example, synovial fibroblasts and progenitor cells in the superficial zone of cartilage could be targeted for p16 INK4a loss with the Prg4 tm1(GFP/cre/ERT2)Abl allele (Kozhemyakina et al., 2015). Lineage tracing studies have suggested that subpopulations of synovial cells harbor regenerative potential (Decker et al., 2017) and a proliferative block in these cells through senescence may limit this capacity with aging. Our findings may have also been influenced by the development of medullary neoplasia with associated bone production in the Acan tm1(cre/ERT2)Crm p16 L/L mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, synovial fibroblasts and progenitor cells in the superficial zone of cartilage could be targeted for p16 INK4a loss with the Prg4 tm1(GFP/cre/ERT2)Abl allele (Kozhemyakina et al., 2015). Lineage tracing studies have suggested that subpopulations of synovial cells harbor regenerative potential (Decker et al., 2017) and a proliferative block in these cells through senescence may limit this capacity with aging. Our findings may have also been influenced by the development of medullary neoplasia with associated bone production in the Acan tm1(cre/ERT2)Crm p16 L/L mice.…”
Section: Discussionmentioning
confidence: 99%
“…These cells exhibit an interesting replicative biology, showing extremely low proliferation rates in adult humans and mice during homeostasis (Aigner et al., 2001; Decker et al., 2017). Chondrocyte proliferation can occur during the development of osteoarthritis (OA) in the form of cell clusters, but it is not known if this replicative response is regenerative, pathologic, or epiphenomenal (Lotz et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Fig. 1 B, Decker et al, 2016). These positively labeled cells and/or their progeny remained in the articular cartilage through at least 6 months of age (Fig.…”
Section: Origin Of Synovial Joint Progenitor Cellsmentioning
confidence: 94%
“…1 A, C, E, Koyama et al, 2008). We recently developed a novel inducible BAC transgenic Gdf5 CreERT2 mouse line, and when the mice were crossed with R26R zsGreen mice, we were able to more selectively, although less abundantly, label specific cell populations (Decker et al, 2016). For example, when tamoxifen was administered at late embryonic time points, Gdf5 CreERT2 + cell labeling was more restricted to cells within the eventual articular cartilage.…”
Section: Origin Of Synovial Joint Progenitor Cellsmentioning
confidence: 99%
“…[112] GDFs, specifically GDF-5, interact closely with BMPs and act as signaling molecules in the growth and differentiation of cartilage, tendon, and ligament. [113117] TGF-βs are prevalent in all of these tissues and are known to play a role in proliferation and stem cell differentiation. [118] In particular, TGF-β is heavily implicated for its role in chondrogenic differentiation and development.…”
Section: Biochemical Factorsmentioning
confidence: 99%